A visita domiciliária realizada pelo enfermeiro no domicílio de candidatos a transplante hepático no Hospital das Clínicas da Universidade Federal de Minas Gerais - Malvina Maria de Freitas Duarte (2011)
The present study aimed to analyze the role of a nurse in a home care program and identify the sociodemographic conditions of transplant candidates which can influence the home care of liver post-transplant patients. This study consisted of prospective, qualitative, and descriptive research carried out in the homes of 100 liver transplant candidates attended to at the Transplants Emergency Clinic of the Clinical Hospital ofthe Federal University of Minas Gerais (UFMG). Recommendations for transplants included ethanolic cirrhosis (31.0%), cryptogenic cirrhosis (24.0%), and post-viral C cirrhosis (21.0%). Within the sample, 70% of the patients were male; 37.0% reside in the greater metropolitan area of the city of Belo Horizonte, Brazil; 47.0% live with their spouse and children; and 68.0% relied on their family and friends as caretakers. As regards the family income, 42.0% received up to one minimum salary, 67.0% hadprofessions classified as general services, bank teller, and military personnel, 66.0% were retired, and 62.0% were illiterate or had only an incomplete elementary education. Although 38.0% had a supplementary health plan, 99.0% of the transplants were to be performed by the Brazilian Sole Health System (SUS). Seventy-three percent of thehomes were privately owned, 56.0% had 5 to 8 rooms, 84.0% had tiled roofs, and 56.0% had ceramic tile floors. In the homes, 81% were well-ventilated; however, mold and infiltration could be identified in 45.0%. Electricity was found in 100.0%, sewage system in 91.0%, treated water in 97.0%, covered water tank in 95.0%, water filter in 77.0%, as well as garbage collection more than four times per week and the presenceof domesticated animals in 59.0% of the homes. The nursing diagnosis, called Damaged Home Maintenance could be detected in 89.0% of the homes, where 65.0% needed home improvements and, in 68.0% of the homes, the maintenance could be executed within one months time. Concerning the level of medical advice provided to the patients, 99.0% did not know what to take on the day of the transplant and 38.0% did not know how to properly store their medications. It can therefore be concluded that home care opens the door for the professional nurse to establish aneducational strategy that involves the patient and his/her family members at home, favors communication, and allows for positive interaction in the evolution of the patients treatment.